2017
DOI: 10.1080/10428194.2017.1357173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cytogenetic risk status on outcomes for patients with acute myeloid leukemia undergoing various types of allogeneic hematopoietic cell transplantation: an analysis of 7812 patients

Abstract: This study aimed at determining how cytogenetic risk status affects outcomes for patients with acute myeloid leukemia (AML) after undergoing various types of allogeneic hematopoietic cell transplantation (HCT). Of 7812 patients eligible for analysis, cytogenetic risk was classified as favorable for 1088, intermediate for 5025, and poor for 1699. Overall, multivariate analysis showed significant intergroup differences in terms of relapse and survival, with the difference between poor- and intermediate-risk grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…A cohort of 7,812 patients was analyzed following their stratification as cytogenetically favorable-, intermediate-, and poor-risk groups as described by the National Comprehensive Cancer Network criteria used to evaluate the prognostic significance of cytogenetic risk in patients undergoing allogeneic HCT. Cytogenetic risk has been shown to have a major impact on post-transplant survival and relapse, and this effect was evident irrespective of donor type, disease status at the time of transplantation and conditioning intensity 9 . The 11q23 chromosomal abnormalities in the KMT2A (formerly known as MLL)gene were detected in approximately 5% of adults with AML, and patients with these abnormalities generally have an unfavorable prognosis.…”
Section: Cytogeneticsmentioning
confidence: 99%
“…A cohort of 7,812 patients was analyzed following their stratification as cytogenetically favorable-, intermediate-, and poor-risk groups as described by the National Comprehensive Cancer Network criteria used to evaluate the prognostic significance of cytogenetic risk in patients undergoing allogeneic HCT. Cytogenetic risk has been shown to have a major impact on post-transplant survival and relapse, and this effect was evident irrespective of donor type, disease status at the time of transplantation and conditioning intensity 9 . The 11q23 chromosomal abnormalities in the KMT2A (formerly known as MLL)gene were detected in approximately 5% of adults with AML, and patients with these abnormalities generally have an unfavorable prognosis.…”
Section: Cytogeneticsmentioning
confidence: 99%
“…The median dose of the total nuclear cell count (TNCC) was 2.54 × 10 7 /kg (range, 0.02-31.0). The cytogenetic risk was classified according to the National Comprehensive Cancer Network Guidelines Version 1.2016 [16], and patients with a favorable risk at the initial diagnosis were excluded. The Institutional Review Board of Jikei University School of Medicine approved this study.…”
Section: Study Populationmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is a heterogeneous disease with different molecular and genetic abnormalities, that define the various disease risk groups. Patients that pertain to an adverse or poor risk group have a dismal outcome, despite allogeneic hematopoietic cell transplantation (allo HCT), with a 5-year overall survival (OS) of 19-46% [1,2]. This dismal outcome is mainly due to the high relapse rate (40-68%) in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of myeloablative conditioning (MAC) with reduced intensity conditioning (RIC) regimens in patients with (poor risk) AML has yielded contradictory results [2,[5][6][7][8][9][10][11]. Some of these studies showed that higher relapse risk with RIC allo HCT was counterbalanced by higher NRM in MAC allo HCT, resulting in comparable OS.…”
Section: Introductionmentioning
confidence: 99%